2020
DOI: 10.1002/rmv.2122
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin‐converting enzyme 2: The old door for new severe acute respiratory syndrome coronavirus 2 infection

Abstract: Summary Coronavirus (CoV) disease 2019 (COVID‐19) is an ongoing pandemic caused by severe acute respiratory syndrome CoV 2 (SARS‐CoV‐2). The highly contagious SARS‐CoV‐2 belongs to the genus Betacoronavirus, and it is phylogenetically closely related to SARS‐CoV, a human CoV that caused an outbreak back in 2002 to 2003. Both SARS‐CoV‐2 and SARS‐CoV enter human cells via the interactions between viral crown‐like spike protein and human angiotensin‐converting enzyme 2 (ACE2) receptor. Here, we aim to review the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(60 citation statements)
references
References 154 publications
(198 reference statements)
0
58
0
2
Order By: Relevance
“…Spike proteins are crown-shaped membrane fusion proteins distributed across the surface of all coronaviruses. Although SARS-CoV and SARS-CoV-2 share similar spike protein and ACE2 receptor-binding sequences, the affinity of the SARS-CoV-2 spike protein for the ACE2 receptor seems to be 10-20-fold higher than that of the SARS-CoV spike protein, suggesting that SARS-CoV-2 has a much higher human-to-human transmissibility than SARS-CoV 53,54 . Following binding to the ACE2 receptor, the transmembrane protease serine 2 (TMPRSS2) 55 induces proteolytic cleavage and 'priming' of the spike protein.…”
Section: Neuroinvasivity Of Sars-cov-2mentioning
confidence: 98%
“…Spike proteins are crown-shaped membrane fusion proteins distributed across the surface of all coronaviruses. Although SARS-CoV and SARS-CoV-2 share similar spike protein and ACE2 receptor-binding sequences, the affinity of the SARS-CoV-2 spike protein for the ACE2 receptor seems to be 10-20-fold higher than that of the SARS-CoV spike protein, suggesting that SARS-CoV-2 has a much higher human-to-human transmissibility than SARS-CoV 53,54 . Following binding to the ACE2 receptor, the transmembrane protease serine 2 (TMPRSS2) 55 induces proteolytic cleavage and 'priming' of the spike protein.…”
Section: Neuroinvasivity Of Sars-cov-2mentioning
confidence: 98%
“…The degree of severity may also be associated to the imbalance of ACE2 and the cytokine storm that results in heart failure progression [ 51 ] [preprint: not peer-reviewed]. Leung et al [ 61 ] found increased ACE2 expression in lower airways of smokers and individuals with chronic obstructive pulmonary disease, but further investigation is required to verify the association between higher lung ACE2 expression and COVID‐19 susceptibility [ 62 ].…”
Section: Ace2 Associations With Several Diseases and Covid-19mentioning
confidence: 99%
“…Since SARSCoV-2 uses ACE2 as the receptor, it is intelligent to expect that every single human cell that expresses ACE2 are the likely focuses for SARSCoV-2 [54]. In this way, the accompanying inquiries with respect to ACE2 articulation comparable to COVID-19 defenselessness can be asked [55,56]: (a) Which parts of the body express ACE2? (b) Which ACE2-communicating organs are inclined to SARS-CoV-2 contamination?…”
Section: Heart Failure and Covid-19mentioning
confidence: 99%